Seeing saw through the criminological lens: popular representations of crime and punishment - Oleson, J.C. (Criminology, criminal justice, law & society, 2015)
Crime is a staple of the media, and violent crimes such as murder are overrepresented in both news and entertainment. Although cases of serial homicide are exceptionally rare, stories about serial killers are terrifically popular. Indeed, while the seven Saw feature films, recounting the crimes of serial killer John “Jigsaw” Kramer, have been derided as mere “torture porn” by some critics, they constitute the most successful horror franchise in the world. Certainly, the Sawfranchise entertains, allowing viewers to vicariously explore their fears of the serial killer in a safe, controlled manner. The Saw films both inform and misinform viewers about crime and punishment—employing parasocial experiences of violent criminal events to prompt viewers to wrestle with fundamental questions of law, morality, and purpose. Viewed through lenses of crime and punishment, the Saw franchise offers both a critique of and commentary on crime in present society. The fictional character of John Kramer can be analyzed through real homicide typologies, and Kramer’s crimes can prompt discussion about the four cardinal philosophies of punishment: retribution, deterrence, incapacitation, and rehabilitation.